Analysis of Patchouli Farmers’ Welfare Using the NTPRP Approach (Policy Implications for Agricultural Development in Ampana Tete District, Tojo Una-Una Regency, Central Sulawesi Province, Indonesia) - Ayu Arini; Saiful Darman; Dian Safitri; Adinda Elfara Rizki Adam (Jurnal Ilmiah Membangun Desa dan Pertanian, 2025)
Patchouli farming plays a crucial role in supporting the rural economy of Central Sulawesi; however, farmers’ welfare remains relatively low. This study aims to analyze the welfare level of patchouli farmers in Ampana Tete District, Tojo Una-Una Regency, using the Household Income Exchange Rate of Farmers (NTPRP) as an indicator of economic well-being. The research location was purposively selected because it is one of the major patchouli-producing areas in Central Sulawesi Province. A quantitative descriptive approach was used to describe the socio-economic conditions of farmers systematically. Data were collected through a census of 15 respondents using structured questionnaires and analyzed by comparing total household income and expenditure using the NTPRP formula. The results show that farmers’ annual household income ranged from IDR 22,500,000 to IDR 36,900,000, with an average of IDR 29,683,650. Of this, 40.54% originated from agricultural activities and 59.46% from non-agricultural sources such as trade, labor, and transportation services. Household expenditure ranged between IDR 38,000,000 and IDR 52,500,000 per year, averaging IDR 46,080,350, with non-food expenses dominating. The calculated NTPRP value of 0.64 indicates that household income is insufficient to meet total expenditure, meaning that farmers have not yet reached a prosperous living standard. This finding implies that diversification of non-agricultural income is essential for sustaining household economic stability. Therefore, local policymakers should design community empowerment programs and support small-scale enterprises to improve the economic resilience of patchouli farmers.